2010
DOI: 10.1161/atvbaha.108.181610
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidases: Functions and Pathologies in the Vasculature

Abstract: Abstract-Reactive oxygen species are ubiquitous signaling molecules in biological systems. Four members of the NADPH oxidase (Nox) enzyme family are important sources of reactive oxygen species in the vasculature: Nox1, Nox2, Nox4, and Nox5. Signaling cascades triggered by stresses, hormones, vasoactive agents, and cytokines control the expression and activity of these enzymes and of their regulatory subunits, among which p22phox, p47phox, Noxa1, and p67phox are present in blood vessels. Vascular Nox enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
523
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(538 citation statements)
references
References 119 publications
8
523
0
7
Order By: Relevance
“…ROS production is increased in VSMCs from resistance arteries of hypertensive patients, and this is associated with up-regulation of vascular Nox (75,112,142,207,213,233). The importance of Nox in human cardiovascular disease is supported by studies showing that polymorphisms in Nox subunits are associated with increased atherosclerosis and hypertension.…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…ROS production is increased in VSMCs from resistance arteries of hypertensive patients, and this is associated with up-regulation of vascular Nox (75,112,142,207,213,233). The importance of Nox in human cardiovascular disease is supported by studies showing that polymorphisms in Nox subunits are associated with increased atherosclerosis and hypertension.…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…Characterization of Noxes as they pertain to vascular biology and hypertension has recently been reviewed. 76,77 In vessels, in addition to vascular cells possessing functional Noxes, resident macrophages, neutrophils and platelets express NAD(P)H oxidase, particularly in pathological states. Accordingly these cells can also contribute to vascular oxidative stress in disease.…”
Section: Vascular Generation Of Rosmentioning
confidence: 99%
“…18 In the vasculature, NADPH oxidases are critical factors for the aberrant ROS production in various disorders. 19 Cumulative evidence indicated that oxidative stress from increased production or insufficient removal of ROS aids the progression of atherosclerosis. 18,19 Our previous study demonstrated that long-term oral estrogen treatment reduces ROS levels and atherosclerosis progression in apolipoprotein E-knockout (apoE-KO) mice, which suggests atheroprotective effects via anti-oxidative actions.…”
mentioning
confidence: 99%
“…19 Cumulative evidence indicated that oxidative stress from increased production or insufficient removal of ROS aids the progression of atherosclerosis. 18,19 Our previous study demonstrated that long-term oral estrogen treatment reduces ROS levels and atherosclerosis progression in apolipoprotein E-knockout (apoE-KO) mice, which suggests atheroprotective effects via anti-oxidative actions. 20 The bioavailability of endothelium-derived NO is negatively modulated by the presence of superoxide, as these two molecules react with high affinity to produce peroxynitrite (ONOO À ).…”
mentioning
confidence: 99%